2012
DOI: 10.1002/jsfa.5857
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high hydrostatic pressure on physicochemical and functional properties of walnut (Juglans regia L.) protein isolate

Abstract: These results suggest that HHP treatment could be applied to modify the properties of walnut proteins by appropriate of pressure levels, which will help in using walnut protein as a potential food ingredient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 36 publications
3
48
0
Order By: Relevance
“…It might also be related to, e.g., hydrophobic aggregation of proteins to form more stable structure in salmon proteins after experiencing extreme pHs (Zhao et al 2015). It has been also previously reported that too high protein denaturing factors like hydrostatic pressure in contrast with moderate pressures reduced surface hydrophobicity of proteins by causing hydrophobic interaction of the proteins (Qin et al 2013). Surface hydrophobicity of all FPPs was lower than for SPI while herring and cod protein powders showed considerably higher surface hydrophobicity than EWP and WPI.…”
Section: Surface Hydrophobicitymentioning
confidence: 89%
See 2 more Smart Citations
“…It might also be related to, e.g., hydrophobic aggregation of proteins to form more stable structure in salmon proteins after experiencing extreme pHs (Zhao et al 2015). It has been also previously reported that too high protein denaturing factors like hydrostatic pressure in contrast with moderate pressures reduced surface hydrophobicity of proteins by causing hydrophobic interaction of the proteins (Qin et al 2013). Surface hydrophobicity of all FPPs was lower than for SPI while herring and cod protein powders showed considerably higher surface hydrophobicity than EWP and WPI.…”
Section: Surface Hydrophobicitymentioning
confidence: 89%
“…It has been also previously reported that extreme pHs used during pH-shift processing of fish proteins can cause unfolding of proteins causing exposure of buried sulfhydryl groups (Abdollahi et al 2017). Further, it was reported that conformational changes and protein denaturation caused by high pressure and freeze-thaw cycles increased active sulfhydryl group content of walnut protein isolate (Qin et al 2013) and SPI (Zhao et al 2015), respectively.…”
Section: Amino Acid Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved foam stability of egg white protein after high pressure application was traced back to enhanced protein-protein interactions (Van der Plancken, Van Loey, & Hendrickx, 2007). Increased foaming ability and stability of pressure treated walnut protein correlated with the degree of unfolding and is thought to arise from a thicker viscoelastic film around the air bubbles (Qin et al, 2013). The formation of fractions with larger molecular weight found in SDS PAGE (see Fig.…”
Section: Foaming Propertiesmentioning
confidence: 99%
“…There is a various of walnuts differing in varieties, productivity, physical and chemical features of their kernel. Some of them have been evaluated as promising and may serve as germplasm sources for breeding (Warmund et al, 2009;Martínez et al, 2010;Qin et al, 2012;Albuquerque et al, 2013). As we all know, the kernel of walnut as food has remarkable nutrients such as quinones, oils, tannins, essential fatty acids, albumin, mucilage, mineral matter, amino acids, and so on.…”
Section: Introductionmentioning
confidence: 99%